2016
DOI: 10.7759/cureus.921
|View full text |Cite
|
Sign up to set email alerts
|

Emergence Delirium With Post-traumatic Stress Disorder Among Military Veterans

Abstract: The clinical characteristics of emergence delirium (ED) associated with post-traumatic stress disorder (PTSD) among military veterans encompass transient agitation, restlessness, disorientation, and violent verbal and physical behaviors due to re-experiencing of PTSD-related incidents. Two cases of ED after general anesthesia associated with PTSD are presented. Different anesthesia methods were applied for the two cases. A traditional medical approach appeared not to prevent the incidence of ED. In the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…After reversible causes are treated, repeat dexmedetomidine loading may also be helpful [ 3 , 4 , 6 , 16 ]. Low-dose propofol boluses may be used to smooth reemergence after a failed initial attempt [ 3 , 4 , 5 , 6 , 12 ]. Small doses of haloperidol may also be administered [ 3 , 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After reversible causes are treated, repeat dexmedetomidine loading may also be helpful [ 3 , 4 , 6 , 16 ]. Low-dose propofol boluses may be used to smooth reemergence after a failed initial attempt [ 3 , 4 , 5 , 6 , 12 ]. Small doses of haloperidol may also be administered [ 3 , 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mixed results of many treatment strategies have demonstrated the multifactorial nature of EA. However, it does appear that dexmedetomidine is consistently helpful in addressing the multifactorial nature of PTSD, as it provides both sedation and analgesia and smooths emergence [3,5,11]. Although expert opinion suggests avoiding benzodiazepines in patients with PTSD, midazolam has been used by most providers in these case reports with varying effects [3,4,6,[11][12][13][14][15].…”
Section: Authormentioning
confidence: 99%
See 1 more Smart Citation
“…33,[43][44][45][46][47][48][49] Dexmedetomidine, when administered prior to emergence (preoperatively, intraoperatively, and/or at the end of surgery), will facilitate cooperative and tranquil patient behavior. 33,36,[38][39][40][41][43][44][45][46][47][49][50][51][52][53][54][55][56] Dexmedetomidine has an onset of 5-10 minutes and duration of 2-3 hours. 20,25 Numerous studies have shown that dexmedetomidine is effective in preventing emergence delirium, 31,[38][39][40][41]46,[48][49][50][51][52][53][54][55][56][57] while few studies indicate that it may be used to treat an episode of emergence delirium.…”
Section: Midazolam (Benzodiazepine)mentioning
confidence: 99%
“…33,36,[38][39][40][41][43][44][45][46][47][49][50][51][52][53][54][55][56] Dexmedetomidine has an onset of 5-10 minutes and duration of 2-3 hours. 20,25 Numerous studies have shown that dexmedetomidine is effective in preventing emergence delirium, 31,[38][39][40][41]46,[48][49][50][51][52][53][54][55][56][57] while few studies indicate that it may be used to treat an episode of emergence delirium. 35,58,59 One study showed that preoperative and intraoperative administration of dexmedetomidine significantly reduced the incidence and severity of emergence delirium among anxiety afflicted combat veterans.…”
Section: Midazolam (Benzodiazepine)mentioning
confidence: 99%